Analisis Perbandingan Produktivitas Material Budidaya Akuaponik Berbasis IoT (Internet of Things) dengan Budidaya Akuaponik Konvensional - Wiradani, Putu Althea Putri; Jasa, Lie; Rahardjo, Pratolo (Majalah Ilmiah Teknologi Elektro, 2022)
Aquaponics is one of the methods of farming in urban areas that produces fish and vegetables at the same time. One aspect that can improve the quality of aquaponics products such as catfish and water spinach in a short period of time is the addition of Internet of Things (IoT) systems. This technology allows farmers to automate work and monitor aquaponics media remotely. Before applying this technology, it is necessary to analyze to what extent each aquaponics system improves the quality of fish and vegetables. The purpose of this study is to compare the productivity of materials needed to grow catfish and water spinach in IoT-based aquaponics and conventional aquaponics. The parameters studied to support the results of the analysis are fish weight and vegetable weight after 14 days. The results show that the weight of fish and vegetables produced by IoT aquaponics is heavier than that produced by conventional aquaponics, which leads to a higher number of production units. It makes the IoT aquaponics productivity percentage value greater with a productivity difference of 112%, which indicates that the IoT aquaponics system manages the required materials more efficiently in a short period of time.